PEDAGOGY OF PRIMARY EDUCATION, UNIQUE FEATURES OF INNOVATION AND INTEGRATION SCIENCE - Atamuratova Nesibeli Davirkhanovna (Journals Park Publishing, 2022)
Education means the physical process as a single process and the soul. the formation of personality, the process of socialization is consciously focused on some ideal images, societies that are historically consolidated in the mind of society. This article discusses about the pedagogy of primary education, unique features of innovation and integration science.
Keywords: pedagogy, primary education, features, uniqueness, innovation, process